Mechanism of Change in Cognitive Behavioral Therapy for Body Image and Self-Care on ART Adherence Among Sexual Minority Men Living with HIV - Lamb, Kalina M. (AIDS Behav, 2018)
Body image disturbance is a common problem reported among sexual minority men living with HIV, and is associated with poor antiretroviral therapy (ART) adherence. Recently, a novel integrated intervention (cognitive behavioral therapy for body image and self-care; CBT-BISC) was developed and pilot tested to simultaneously improve body image and ART adherence in this population. Although CBT-BISC has demonstrated preliminary efficacy in improving ART adherence, the mechanisms of change are unknown. Utilizing data from a two-armed randomized controlled trial (N = 44 sexual minority men living with HIV), comparing CBT-BISC to an enhanced treatment as usual (ETAU) condition, sequential process mediation via latent difference scores was assessed, with changes in body image disturbance entered as the mechanism between treatment condition and changes in ART adherence. Participants assigned to CBT-BISC reported statistically significant reductions in body image disturbance post-intervention, which subsequently predicted changes in ART adherence from post-intervention to long term follow-up (b = 20.01, SE = 9.11, t = 2.19, p = 0.028). One pathway in which CBT-BISC positively impacts ART adherence is through reductions in body image disturbance. Body image disturbance represents one, of likely several, mechanism that prospectively predicts ART adherence among sexual minority men living with HIV.